Dual Anti-Inflammatory and Anticancer Activity of Novel 1,5-Diaryl Pyrazole Derivatives: Molecular Modeling, Synthesis, In Vitro Activity, and Dynamics Study - Priya Deivasigamani; S. M. Esther Rubavathy; Narayanan Jayasankar; Venkatesan Saravanan; Ramasamy Thilagavathi; Muthuramalingam Prakash; Chelliah Selvam; Rajakrishnan Rajagopal; Ahmed Alfarhan; Muthu Kumaradoss Kathiravan; Selvaraj Arokiyaraj; Jesu Arockiaraj (Biomedicines, 2024)
A series of novel 1,5-diaryl pyrazole derivatives targeting the COX enzyme were designed by combined ligand and structure-based approach. The designed molecules were then further subjected to ADMET and molecular docking studies. Out of 34 designed compounds, the top-10 molecules from the computation studies were synthesized, characterized, and evaluated for COX-2 inhibition and anti-cancer activity. Initially, the target compounds were screened for the protein denaturation assay. The results of the top-five molecules T2, T3, T5, T6, and T9 were further subjected to in vitro COX-2 enzymatic assay and anti-cancer activity. As far as COX-2 inhibitory activity is considered, two compounds, T3 and T5, exhibited the half maximum inhibitory concentration (IC50) at 0.781 µM and 0.781 µM respectively. Further, the two compounds T3 and T5, when evaluated for COX-1 inhibition, exhibited excellent inhibitory activity with T3 IC50 of 4.655μM and T5 with IC50 of 5.596 μM. The compound T5 showed more significant human COX-2 inhibition, with a selectivity index of 7.16, when compared with T3, which had a selectivity index of 5.96. Further, in vitro anti-cancer activity was screened against two cancer cell lines in which compounds T2 and T3 were active against A549 cell lines and T6 was active against the HepG2 cell line. Stronger binding energy was found by comparing MM-PBSA simulations with molecular docking, which suggests that compounds T3 and T5 have a better possibility of being effective compounds, in which T5 showed higher binding affinity. The results suggest that these compounds have the potential to develop effective COX-2 inhibitors as anti-cancer agents.